Reflexión sobre la mediación pedagógica de la enseñanza de las Matemáticas con personas jóvenes y adultas - Víquez Ortiz, María Fernanda (2020)
The implementation of an appropriate action for young people and adults in the teaching of Mathematics in the country has been a perennial need. The characteristics of these individuals differ greatly from those of children and young people who attend another type of educational offering. The foregoing has even more repercussions, when the country and its teachers are immersed in the health emergency, due to Covid-19; where neither the student population nor the teaching staff were prepared for distance education. Consequently, the need for the teaching of Mathematics to develop from previous experiences and using Information and Communication Technologies, with the aim of promoting meaningful learning and skills throughout life, increases.